Flexible Electronics: Substrate‐Versatile Direct‐Write Printing of Carbon Nanotube‐Based Flexible Conductors, Circuits, and Sensors (Adv. Funct. Mater. 25/2021). (17th June 2021) - Owens, Crystal E.; Headrick, Robert J.; Williams, Steven M.; Fike, Amanda J.; Pasquali, Matteo; McKinley, Gareth H.; Hart, A. John
Abstract : In article number 2100245, Crystal E. Owens, Gareth H. McKinley, A. John Hart and co‐workers present a direct‐write printing process controlled by two parameters to extrude aqueous carbon nanotube (CNT) solutions with liquid crystalline behavior, drawing highly conductive and flexible traces, sensors, and circuits with integrated circuit elements onto a variety of flexible substrates. The high CNT concentration and lack of fillers allow high final conductivity.